KEDUDUKAN ANAK DI LUAR PERKAWINAN YANG SAH DITINJAU DARI HUKUM ADAT BALI - Nyoman Widyani; Ni Putu Yuliani Dewi (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2019)
The purpose of this study were: (1) to determine the cause of the birth of a child outside marriage were legal in Bali, (2) to determine the position of a child outside of marriage is valid in terms of customary law of inheritance Bali, (3) to know the effort that can be done so that families of children born outside marriage can be a legitimate child seen from the customary law of Bali. This study uses Ethnographic approaches in qualitative research paradigm. The technique of determining the subject of research using purposive sampling technique and the subject of this research is the village head / prebekel, Bendesa Peoples, Kelian Adat, Kelian Dinas, community leaders, women who experienced cases, men who impregnate, and women's families. Data collection techniques used in this study: (1) observation, (2) Interview (3) the recording document. Techniques of data analysis conducted with qualitative research approaches in the form of description. The results showed that (1) birth of a child outside of marriage is valid because the promiscuity, the relationship between men and women outside of wedlock, and before the religious ceremony was held, (2) in the customary law of Bali child outside of marriage has no legal status and do not have a status that is often referred to as a child bebinjat and could not enter the clan's father and mother both customary (3) the efforts made by Balinese customary law and religion, status of children can be pursued by implementing meperas ceremony where the child can be raised by one of the families so that children have a legal status, so that if a child has been raised through meperas ceremony would be considered a legitimate child of parents who picked it up.